The Association of Household Waste Management with the Risk of Scabies Incidence in Endemic Areas - Idham Halid; Muhammad Nawawi; Musparlin Halid (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Scabies is a contagious skin disease that remains a public health problem in endemic areas, especially in environments with poor sanitation and waste management. Ecosystem-based household waste management is believed to contribute to the prevention of environment-based diseases through improvements in sanitation and community behavior. This study aims to analyze the relationship between ecosystem-based household waste management and the risk of scabies in endemic areas, as well as to identify factors that play a significant role in its transmission. Methods: The study used a cross-sectional design with 248 respondents from households in an area endemic for scabies, namely Rumak Village, West Lombok, Indonesia. Data were collected through structured interviews and field observations using a standardized questionnaire. Data analysis used the Chi-square test and logistic regression to determine the dominant factors associated with the incidence of scabies. Results: A total of 39.1% of respondents reported having experienced scabies. Logistic regression analysis showed that the most influential factors affecting the incidence of scabies were poor local final waste management (p=0.001), followed by lack of waste sorting (p=0.004), presence of pets (p=0.004), and lack of organic composting (p=0.008). Other significant factors included poor personal hygiene (p=0.008) and low knowledge about scabies (p=0.023). Conclusion: The results of the study confirm that ecosystem-based household waste management plays an important role in reducing the risk of scabies. Good environmental management practices, accompanied by hygienic behavior and increased public knowledge about scabies, are effective strategies for controlling this disease in endemic areas.